EMPOWERING THE MILLENNIAL: THE STRATEGIC ROLE OF PSYCHOLOGICAL CAPITAL AND GRIT IN THE WORKPLACE - Rengganis, Domnina Rani Puna; Rusdi, Fairuz A’Dilah; Raston, Nursalihah Ahmad; Mohamad, Nurul Muna (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
As millennials have emerged as the predominant cohort in the contemporary workforce, organizations are strategically required to strengthen psychological resources that facilitate sustained performance and retention. Accordingly, this study investigates the impact of Psychological Capital (PsyCap) a higher-order construct comprising hope, self-efficacy, resilience, and optimism on the formation of grit among millennial employees. This study employed a quantitative research design with a sample of 116 millennial employees selected through purposive sampling. Data were collected using the Revised Compound Psychological Capital Scale (CPC-12R) and the Short Grit Scale (Grit-S). The hypothesis was tested using simple linear regression analysis after confirming the assumptions of normality, linearity, and homoscedasticity. The findings revealed that psychological capital has a significant and positive influence on grit (F (1, 114) = 108.210, p < .001). The model summary showed an R-squared value of .487, indicating that PsyCap explains 48.7% of the variance in grit. Descriptive statistics showed that while all participants had high levels of grit, their PsyCap levels were evenly distributed between medium (50%) and high (50%), highlighting PsyCap as a key differentiating factor. The study provides strong empirical evidence that psychological capital is a significant antecedent to grit in the workplace. The results suggest that organizations can strategically empower their millennial workforce by implementing targeted interventions, such as training and coaching, to develop PsyCap. Fostering these core psychological resources presents a practical pathway to enhancing employees' perseverance and passion, ultimately leading to improved performance and long-term commitment.